Performance modeling for a Web GRID architecture - Bajrami, Agim; Zdraveski, Vladimir; Filiposka, Sonja; Piskachev, Goran; Trajanov, Dimitar (IEEE, 2011)
There are a lot of P2P computing systems or distributed GRID systems that have clients that need to be downloaded and installed on the client’s computer and after that they will start with their work for the grid computation. Unlike this approach, there is another type of grid processing clients, which are based on web browsers. These Web GRID systems are easier to use, because they don’t require manual download and installation. Users are only one click away of involving in the grid computing process. In this paper, we are analyzing the Web GRID solutions and propose a Web GRID architecture for which we present a mathematical performance modeling. We also emphasize the GRID user interface gains, the expected increase of the number of the future GRID worldwide users and claim the problems found in our Web GRID show-case scenario implementation.
Keywords: GRID, User, WEB, Web Client script